The decision-making process in public healthcare entities - identification of the decision-making process type = Proces podejmowania decyzji w publicznych podmiotach leczniczych - identyfikacja typu procesu decyzyjnego - Szymaniec-Mlicka, Karolina (Zielona Góra: Faculty of Economics and Management Press)
The decisions made in the organization determine its success, therefore, conducting studies in the scope of decision-making seems important both for theory and practice. The aim of the studies was to identify the type of decision-making process in public medical entities with the use of typology developed by P. Nutt. For this purpose we used qualitative methods.
Keywords: proces podejmowania decyzji; organizacja publiczna; Szpital; decision-making; public organization; hospital